Manajemen Risiko Kredit Dalam Meminimalisir Risiko Ketidakmampuan Pembayaran Debitur Di PT. BPR Wutama Artha Jaya Jember - Intan Mustikawati Putri; Silvi Salavi Sauqina; Sofiatul Munawaroh; Ayyu Ainun Mustafidah (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
Credit Risk Management Approach in Minimizing the Risk of Debtor Inability to Pay at PT. BPR Wutama Artha Jaya Jember is still less relevant due to bad credit caused by several influencing factors and a lack of accountability on the part of the debtor, thus affecting the financial reporting entity, the profits generated and the impact on the bank's health. The purpose of this research is to determine the procedures for granting PT credit. BPR Wutama Artha Jaya Jember and its relationship to the problems that occur. The methods used are the Literature Study Method and the Qualitative Method. The results of this research are that to overcome bad credit at PT. BPR Wutama Artha Jaya is giving fines and for debtors who experience delays in payments as punishment for debtors so that debtors will be more disciplined in subsequent payments. The procedures for handling bad credit at BPR Wutama can be said to be poor due to the presence of irresponsible debtors, as evidenced by the periodic increase in NPL from quarterly reports, however, with the principle of prudence in following up on bad credit, efforts are still being made to handle bad credit. . And it is best for bank officers to carry out credit analysis in accordance with the established SOPs and in accordance with the actual situation, as well as emphasizing the performance of debtor development in order to minimize the risks that occur due to problem loans.